1999
DOI: 10.1002/(sici)1520-6823(1999)7:6<353::aid-roi5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal treatment volume in Hodgkin's disease patients undergoing high-dose chemotherapy and adjuvant radiation therapy?

Abstract: To determine the optimal treatment volume in Hodgkin's disease patients undergoing high‐dose chemotherapy (HDCT) and radiation therapy (RT), failure sites were reviewed in 56 patients. Twenty‐one (38%) received involved‐field RT (IFRT) before or after HDCT encompassing sites of prior disease. Failure sites were designated as previously involved (old) or uninvolved (new) sites. Seven patients (12%) died in the immediate post‐HDCT period, leaving 49 evaluable (median follow‐up, 41 months). Twenty‐five patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…8 In another study, it is suggested that adjacent uninvolved sites are at risk of failure when involved fields are strictly confined to known sites of HD in a transplant setting. 59 In the present series, we found that relapse in adjacent sites occurred in the lung in the presence of extensive mediastinal disease, but we found no cases of isolated adjacent nodal failure.…”
Section: Discussioncontrasting
confidence: 47%
“…8 In another study, it is suggested that adjacent uninvolved sites are at risk of failure when involved fields are strictly confined to known sites of HD in a transplant setting. 59 In the present series, we found that relapse in adjacent sites occurred in the lung in the presence of extensive mediastinal disease, but we found no cases of isolated adjacent nodal failure.…”
Section: Discussioncontrasting
confidence: 47%